VERTICAL-HORIZONTAL WATER QUALITY PROFILES OF BATUR LAKE, BANGLI DISTRICT, BALI SUPPORTING SUSTAINABLE LAKE MANAGEMENT - Sophia Sagala; I Nyoman Radiarta (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
Batur Lake located in Bangli District is one of fisheries-basedregions in Bali with niletilapia as the main cultured species. Monitoring on environmental conditions of the lake was carried out to get the vertical and horizontal water quality profiles of the lake. Climatology condition of the area was also presented in the study. The study area were between 8o13’-8o18’ S and 115o22’-115o26’ E. Field survey was done with random and transect sampling points distribution. The water quality monitored in the lake essential ly covers important parameters such as depth, transparency, temperature, pH, dissolved oxygen, salinity, nutrients (ammonia, nitrate, nitrite, and phosphate), sulfide, chlorophyll, and planktonic composition. Results of spatial analysis (vertically and horizontal ly) of water quality indicated that oxygen concentration up to 10 m deep is still appropriate for nile tilapia culture. Nutrient (phosphate, ammonia, nitrate, and nitrite) contents of the lake meet the standard levels set by Ministry of Environment of Indonesia, and were still suitable for aquaculture operation at depth 710 m. From climatology point of view, it is known that the extreme climate occurred in June-August resulting in water mass changes, thus, affecting aquaculture sustainability in the lake.